Petrogenesis of mafic granulite in South Altyn Tagh, NW China: Constraints from petrology, zircon U–Pb chronology, and geochemistry. (24th March 2019) - Li, Yunshuai; Zhang, Jianxin; Li, Yanguang; Mostofa, Khan M.G.; Yu, Shengyao; Guo, Jing; Dong, Juan; Peng, Yinbiao; Jin, Mengqi; Zhou, Guisheng
Abstract : Mafic granulite, garnet peridotite, and garnet pyroxenite occurred as slices or lenses within dominant felsic granulite, and they together constitute a high‐pressure metamorphic terrane in the Bashiwake unit, South Altyn Tagh, Northern Tibet, China. Previous studies focused on the metamorphic evolution, and geothermobarometry results indicated that the mafic granulite has experienced high pressure/(ultra‐)high temperature (HP/(U)HT) metamorphism, followed by a medium pressure (MP) granulite‐facies overprint. However, the nature and petrogenesis of the mafic granulite in the dominant felsic granulite are poorly known. Combining the previous geothermobarometry results with the petrographic observations, mineral chemistry, and pseudosection modelling in this study, at least four stages were suggested for the metamorphic evolution of the mafic granulites in the South Altyn Tagh, including the eclogite‐facies stage (3–4 GPa, 910–1000°C), high pressure–ultrahigh temperature (HP–UHT) metamorphism, an isothermal decompression, and subsequent MP granulite‐facies overprint. The U–Pb dating of zircons yielded two age clusters: one age cluster at ca. 500 Ma, representing the retrograde age of HP–UHT metamorphism after the eclogite‐facies stage, and another age cluster of ca. 900 Ma that represented the age of the protolith for the mafic granulite. This indicated that the protolith of the mafic granulite was formed in the early Neoproterozoic and then was taken to extreme temperatures and pressures during the early Palaeozoic orogenic event. The elemental abundances of the mafic granulites in the Bashiwake area clearly indicated that they were higher in FeO and TiO2, but were significantly lower in MgO, Cr, and Ni than those of associated garnet peridotites/pyroxenites, and they showed LREE‐enriched patterns with slightly positive Eu anomalies. Sr–Nd isotopic data suggested a basaltic magmatic origin with crust contamination for the protolith of the mafic granulite. Integrating these results together with previous studies, we suggest that the mafic granulites were derived from the basaltic magma intrusion in the continental crust during the Neoproterozoic and subsequently suffered a common HP/UHT metamorphism with felsic crust rocks in the early Palaeozoic (ca. 500 Ma) after the eclogite‐facies metamorphism related to the continental collision (>500 Ma).